THE INVESTIGATION OF VASCULAR STIFFNESS IN PATIENTS DEPENDING ON DIFFERENT DEGREES OF ARTERIAL HYPERTENSION - Zolotaryova, N.A.; Vastyanov, R.S. (World of Medicine and Biology, 2024)
The purpose of the study was to investigate the dependence of vascular stiffness on blood pressure level in patients with arterial hypertension. 90 people were included into the clinical observation. These patients were randomized into 2 groups. The group 1 was consisted of 15 healthy individuals The group 2 was consisted of 75 patients with arterial hypertension of various degrees. Pulse wave velocity was measured in all patients. The correlation between pulse wave velocity vs age and systolic/diastolic blood pressure was calculated. The data obtained allowed to state that pulse wave velocity index has tight connection with blood pressure values. The authors reveal high statistical correlation between pulse wave velocity index and blood pressure values. The authors suppose that arterial stiffness might be the earlier diagnostic tool for to approaching vascular accident and, therefore, propose the pulse wave velocity index measurement in patients with initial signs of arterial hypertension.